KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DITINJAU DARI KONSENTRASI BELAJAR PADA MATERI STATISTIKA DASAR - Khoirunnisa Cahani; Kiki Nia Sania Effendi; Dadang Rahman Munandar (IKIP Siliwangi, 2021)
The purpose of this article is to describe student’s mathematical understanding concept abilities based on concentration of learning. This research uses a qualitative approach with descriptive methods. The subjects of this study were students of class VIII at one of junior high schools in Karawang and then choose 3 people based on considerations made by researchers through purposive sampling and through the levels concentration of learning, namely high, medium, and low. Data collection techniques in this study used a mathematical understanding concept abilities test, and concentration of learning questionnaires. The results of the study based on the analysis that has been done show that: students in the category of high learning concentration can fulfillall indicators of the ability understanding mathematical concepts, students in the category of middle learning concentration can fulfill 2 indicators of the ability understanding mathematical concepts, and students in the category of low learning concentration can fulfill 1 indicator of the ability understanding mathematical concepts.